Dirichlet Problem for an Axisymmetric Potential in a Simply Connected Domain of the Meridian Plane - Plaksa, S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We develop a method for the reduction of the Dirichlet problem for an axisymmetric potential in a simply connected domain of the meridian plane to a Cauchy singular integral equation. In the case where the boundary of the domain is smooth and satisfies certain additional conditions, we regularize the indicated singular integral equation.